Development and Validation of an Online Teaching Effectiveness Questionnaire for Online Instructors - Khodarahmi, Somayeh; Hassanirad, Toraj; Safari, Nooshafarin; Hafezi, Hossein (Assessment and Practice in Educational Sciences, 2026)
Given the lack of measurement tools for assessing the level of online teaching effectiveness among online instructors, the present study aimed to validate the Online Teaching Effectiveness Questionnaire for online instructors. The current study was conducted using an analytical instrument-development approach. For this purpose, 345 online instructors who had studied virtually were selected through available random sampling and responded to the Online Teaching Effectiveness Questionnaire. The validity of the instrument was then assessed using content validity, exploratory factor analysis, and confirmatory factor analysis, and its reliability was evaluated using Cronbach’s alpha and test–retest reliability. The results of the factor analyses showed that the factorial structure of the instrument had an acceptable fit with the data and that all goodness-of-fit indices supported the model. Moreover, the reliability analysis indicated that both Cronbach’s alpha coefficients and the test–retest reliability coefficients were all above 0.80, demonstrating appropriate internal and external consistency. Therefore, this questionnaire appears to be a suitable instrument for measuring the level of online teaching effectiveness among online instructors.